Development and validation of the scale of aesthetics and creativity in chess - Scherbakova, Alisa; Engelhard, George; Bahar, A. Kadir (Frontiers in Psychology, 2025)
This study examined the psychometric quality of the Scale of Aesthetics and Creativity in Chess (SACC) with the data collected from 132 expert and non-expert chess players. To analyze the validity, reliability, and item functioning within the scale, the Many-facet Rasch model was applied. The Rasch measure explained 50.59% of the variance in scores and provided evidence for the scale’s unidimensionality. The reliability indices for items and participants were 0.83 and 0.93, respectively. The expertise level of chess players predicted scores on the SACC; however, Intermediate level players showed the lowest scores in comparison with Expert, Advanced, and Beginner level participants.